Uso da restrição hídrica na inoculação de Colletotrichum lindemuthianum em sementes de feijoeiro (Phaseolus vulgaris L.) - Carvalho, João Custódio Barbosa de (1999)
The present research was carried out aiming at to develop a more efficient methodology to inoculate Colletotrichum lindemuthianum in bean seeds by using the hidric restriction principie. The research work was conducted in tree steps. In the fist part, the effect ofdifferent hidric restriction leveis on PDA médium amended with PEG 6,000 or mannitol on the seed radicle emission was investigated. In the second step growth of C. lindemuthianum on PDA containing the PEG 6,000 or mannitol was measured. The third part ofthe work consisted ofevaluating the infection levei obtained by keeping the bean seeds in contact with colonies of C. lindemuthianum, 5 days old, developed on PDA médium amended with mannitol at different concentrations. The results showed that incorporation ofmannitol solution at -IMPa into PDA médium with 5 day incubation, proved to be efficient to obtain higher leveis ofbean seeds infected by the anthracnosis fungous. Growth ofC lindemuthianum was not affected by the hidric restriction produced by the addition ofmannitol, at the maximum levei of -1,0 MPa, into PDA médium. Incorporation of solutions of PEG 6,000 at hidric restrictions higher than -0,6 MPa into PDA caused reduction in the development of C .lindemuthianum. Radicle emission of bean seeds was efficiently impeded on PDA médium containing such components, at hidric restriction leveis of -IMPa for 168 hours.